COVID-19: Factors associated with symptoms of anxiety and depression in the ICU - Laura Andrea Díaz-Mayorga; Harol Giovanni Vivas-López; Claudia Consuelo Torres Contreras; Lyda Z. Rojas; Norma C. Serrano; Angie Yarlady Serrano-García; Margarita Rosa Parra Ortiz; Doris Cristina Quintero-Lesmes (Revista Cuidarte)
Introduction: The COVID-19 pandemic led to a high prevalence of anxiety and depression among healthcare personnel. Objective: To assess the prevalence and independent risk factors associated with anxiety and depression symptoms among healthcare staff working in Intensive Care Units (ICUs) during the COVID-19 pandemic in Bucaramanga and its metropolitan area. Materials and Methods: This was an analytical cross-sectional study. Anxiety and depression were measured using the Hopkins Symptom Checklist-25 (HSCL-25). Bivariate and multivariate analyses were conducted using linear regressions to investigate associated factors. Results: A total of 288 people were included in the study. The prevalence of anxiety and depression symptoms was 8.34% (95% CI: 5.41-12.14%). In the bivariate analysis, six factors were associated with depression and anxiety symptoms; however, only three remained in the multivariate analysis: female sex (β=0.085, 95% CI; 0.019 - 0.151), experiencing COVID-19 symptoms in the past 14 days (β= 0.115, 95% CI: 0.024 - 0.205), and having worked in general ICUs and COVID-19 ICUs (β =0.009, 95% CI: 0.025 - 0.173). Discussion: The prevalence of anxiety and depression symptoms was considerably lower than reported in the scientific literature. Conclusions: In the studied population, although the prevalence of depression and anxiety symptoms was low, three independent factors were found to be statistically associated with the presence of these mental symptoms.